Seroprevalence Of Leptospirosis in South Gujarat Region by Evaluating the Two Rapid Commercial Diagnostic Kits Against the Mat Test for Detection of Antibodies to Leptospira Interorgan - Panwala, Tanvi; Mulla, Summaiya; Patel, Parul (National Journal of Community Medicine, 2011)
The study was conducted to evaluate the two rapid tests for the serologic diagnosis of leptospirosis namely Microplate Immunoglobulin M(IgM)-Enzyme Linked Immunosorbent Assay(ELISA) and IgM Rapid Leptocheck WB and the performance of each assay compared with that of the current standard, the microscopic agglutination test (MAT). The panels of 188 sera from 130 cases of leptospirosis from three different geographical locations were tested as well as 310 sera from healthy individual or individual with other infectious disease other than leptospirosis. Acute phase sera from cases (n=130) were collected <14 days after the onset of symptoms and convalescent phase sera (n=58) were collected ≥14 days after the onset of symptoms. By traditional method (two-by-two) contingency table, the sensitivity, specificity, PPV(Positive predictive value), NPV(Negative predictive value), Efficiency of test and (Kappa) value for agreement (with MAT) for the Rapid Leptocheck WB were 98.36%, 86.95%, 86.95%, 98.36%, 92.37% and 0.81 in acute phase of disease. Corresponding values for IgM ELISA were 96.82%, 88.05%, 88.40%, 96.72%, 91.53% and 0.88 respectively. The sensitivity, specificity, PPV(Positive predictive value), NPV(Negative predictive value), Efficiency of test and (Kappa) value for agreement (with MAT) for the Rapid Leptocheck WB were 87.87%, 88%, 90.82%, 84.61%,86.20% and 0.85 in convalescent phase of the disease. Corresponding values for IgM ELISA were 91.42%, 95.65%, 96.96%, 88%, 93.10% and 0.81 respectively. These values for the 2 tests were comparable, indicating that there was no difference in their efficacies. The second-generation assay included in study (Leptocheck and ELISA) showed significantly higher sensitivity with early acute phase sera than the reference or first generation method (MAT) while retaining high specificity and should greatly improve the rapid detection of leptospirosis in the field.